Pembinaan E-Commerce Dan Desain Kemasan Dalam Peningkatan Profitabilitas Usaha - Andrianto Prasetya Nugroho; Sesri Sellina; Zulfa Zakiatul Hidayah; Prasetyo Hari Sandi; Nadia Meirani (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
The business world is a zone of uncertainty, to survive we must have value or competitiveness. One strategy to increase competitiveness is to adapt to current developments. In this digital era, we can use e-commerce marketing media as a place to sell. Apart from marketing and sales media, there is also an important thing that attracts customers, namely packaging. A common problem that occurs in the business world in this era of digitalization is not being able to adapt to technology, this is also an obstacle for the business world today. So the aim of this community service activity is to provide assistance and guidance in using the online e-commerce sales platform. Apart from that, to increase product value we will provide insight into packaging design with the ultimate goal for business actors to increase productivity and profitability of course. In this case, the method used is direct counseling and guidance at the Cyqul Food business location in Harjamekar Village, North Cikarang. Guiding the use of e-commerce and developing packaging design is very necessary to improve business.